CD8+ T-Cell Mediated Control of HIV-1 in a Unique Cohort With Low Viral Loads - Jones, Amber D.; Khakhina, Svetlana; Jaison, Tara; Santos, Erin; Smith, Stephen; Klase, Zachary A. (Frontiers in Microbiology, 2021)
A unique population of HIV-1 infected individuals can control infection without antiretroviral therapy. These individuals fall into a myriad of categories based on the degree of control (low or undetectable viral load), the durability of control over time and the underlying mechanism (i.e., possession of protective HLA alleles or the absence of critical cell surface receptors). In this study, we examine a cohort of HIV-1 infected individuals with a documented history of sustained low viral loads in the absence of therapy. Through in vitro analyses of cells from these individuals, we have determined that infected individuals with naturally low viral loads are capable of controlling spreading infection in vitro in a CD8+ T-cell dependent manner. This control is lost when viral load is suppressed by antiretroviral therapy and correlates with a clinical CD4:CD8 ratio of less than one. Our results support the conclusion that HIV-1 controllers with low, but detectable viral loads may be controlling the virus due to an effective CD8+ T-cell response. Understanding the mechanisms of control in these subjects may provide valuable understanding that could be applied to induce a functional cure in standard progressors.